Estudio de factibilidad para la creación de la empresa de servicios centro de entrenamiento de juegos electrónicos en la ciudad de Quevedo, los ríos en el año 2011 - García Quirola, Julio Cesar (2011)
Across enterprise, no matter its size required an enabling it to establish the viability of the investment project feasibility study; this is essential to pay attention to fluctuations in the market, the competition, the volume of demand, analysis of the product or service provided by the company, among others; these essential factors allow you to define a broad, global business strategy. It noted that the feasíbility study is a system that can be defmed as a set of resources arranged in tándem to achieve any or some objectives that, at least in part, are economic in nature. At the same time, it can be reasonably analyzed and evaluated as a sepárate unit. Is also important to note that the fundamental in business decisions to an investment project is proper planning, to make a good survey of the pros and cons are may evalúate in a way a priori the goals you want to get out of expenditure since these are in fact which should be in the implementation of a project or investment projects. Within the investigative proposal here is located in located in the Street and 10th sixth Cantón Quevedo 7 October, province of The Rivers. The objectives were: • Study the feasibility for the creation of the company services of a Centro de Entretenimiento de juegos electrónicos in the city of Quevedo in 2010. • Design the matrix log frame for addressing administrativo project. • Perform a diagnostic analysis of market for the acceptance of the project • Determine the study for demonstrating the feasibility of the project.   At the same time made the following hypothesis: For the creation of a promotional company and development of entertainment of video games electronics in the city of Quevedo feasibility study allows determining the profitability. The methodological addressing was oriented on the use of three types of research: de field, descriptive and Correlacional used the techniques of the survey and direct observation applied indüctive, Deductive, analytical methods and synthesis, whose livelihood is achieved through primary and secondary sources based on methods and tools of research information. For the viability of the project for the creation of the promotional company and development of videos games in the city of Quevedo was market study, the technical-commercial study and financial evaluation, so encrust by means of a questionnaire to a significant Quevedeña; citizenship sample highlighting 78.6 % of those surveyed responded that if they would like there to be an enterprise customers a complete and quality service. By another part the Company to créate, must be a total investment of $ 79300, of which 100% of the total is equity. And I our investment recovery time will be 1 year 279 days, since the first year revenues are $ 48049.06 and $ 59644.00 second year giving a total of $12.412,50. We consider the installation of this micro contributes to the economic development of the Cantón in Quevedo for the jobs source and to educate the users serving them with a good customer service.